2012
DOI: 10.2139/ssrn.2133179
|View full text |Cite
|
Sign up to set email alerts
|

Family and Labor Market Choices: Requirements to Guide Effective Evidence-Based Policy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…First, the negative work incentives of in-work support concern second earners in couples (and not lone mothers). Second, the gender employment gaps in Poland, as in many other countries of Central and Eastern Europe (CEE), are strongly related to the demographic structure of the household and childcare responsibilities and are particularly visible among men and women with children (Myck, Kurowska & Kundera, 2013;Kurowska, Myck & Wrohlich, 2012). Myck et al, 2013;Myck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First, the negative work incentives of in-work support concern second earners in couples (and not lone mothers). Second, the gender employment gaps in Poland, as in many other countries of Central and Eastern Europe (CEE), are strongly related to the demographic structure of the household and childcare responsibilities and are particularly visible among men and women with children (Myck, Kurowska & Kundera, 2013;Kurowska, Myck & Wrohlich, 2012). Myck et al, 2013;Myck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that certain family policy instruments impose high marginal tax rates on secondary earners in couples (usually women) and therefore discourage them from taking up or resuming employment. These instruments include in-work family/child tax credits (Eissa and Hoynes, 2004; Brewer et al , 2006; Haan and Myck, 2007; Bar and Leukhina, 2009) and family benefits/allowances (Kornstad and Thoresen, 2007; Laroque and Salanié, 2008; for a review of other instruments see Kurowska et al , 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…First, the negative work incentives of in-work support concern second earners in couples (and not lone mothers). Second, the gender employment gaps in Poland, as in many other countries of Central and Eastern Europe (CEE), are strongly related to the demographic structure of the household and childcare responsibilities and are particularly visible among men and women with children (Myck, Kurowska & Kundera, 2013;Kurowska, Myck & Wrohlich, 2012).…”
Section: Making Work Pay: Increasing Labour Supply Of Secondary Earners In Low Income Families With Childrenmentioning
confidence: 99%